Celebrating family day: Otorhinolaryngology, Faculty of Medicine & Hospital Al-Sultan Abdullah, UiTM - Zahari, Nur Islam; Abdul Rahim, Norazila; Mansor, Masaany; Din, Sobani; Ahmad @ Mohd, Azrina (Faculty of Medicine, 2025)
On 11th January 2025, the Department of Otorhinolaryngology, Head and Neck Surgery (ORL- HNS), Faculty of Medicine & Hospital Al-Sultan Abdullah (HASA), UiTM, successfully organized its first Family Day for the staff of the department.